Open STM: A low-cost scanning tunneling microscope with a fast approach method - Weilin Ma (HardwareX, 2024)
In this study, we have developed an low-cost scanning tunneling microscope (STM) cost of 300 USD or 2000 CNY. The microscope is suitable for educational purposes and low-demand research imaging at the nanometer level. The microscope's motion components and scanner are controlled using piezoelectric materials, avoiding the thermal drift associated with traditional motor control. Our tip approach algorithm, which considers the capacitance and friction characteristics during piezoelectric slider movement, has reduced the time required for sample loading to establish tunneling current to approximately 1 min. The physical dimensions of the microscope body are 45 × 45 × 31.5 mm (W × L × H), and the control voltage does not exceed 15 V, ensuring the safety of operators, particularly those with limited experience. During performance verification, we conducted a scanning tunneling scan on a Highly Oriented Pyrolytic Graphite (HOPG) sample, utilizing bias voltages of 50 mV and 60 mV, resulting in clear observations of the atomic features of HOPG within the STM pattern.